Effect of Calcination Temperature on the Powder of Freshwater Snail Shells (Sulcospira testudinaria) Properties - Nugroho, Bintoro Siswo; Wahyuni, Dwiria; Asri, Asifa; Mustafa, Usliana (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2023)
Gastropod shells, such as those from the freshwater snail (Sulcospira testudinaria), have garnered interest as potential sources of calcium precursors. These shells are rich in calcium carbonate (CaCO3), which can be thermally decomposed into calcium oxide (CaO) through calcination. However, more information is needed on optimizing calcium extraction from the Sulcospira testudinaria (SST) shells. This study aims to investigate the influence of calcination temperature on the characteristics of powder of these shells. The study involves two sample treatments: uncalcined shells and shells calcined at temperatures ranging from 500°C to 1100°C for 1 hour. Fourier transform infrared spectroscopy (FTIR) analysis of uncalcined shell powder revealed the presence of aragonite functional groups within the CaCO3 structure. X-ray diffraction (XRD) analysis provided insights into the transformation of crystalline phases of CaCO3, starting from aragonite to calcite and eventually to calcium oxide, explaining the material's weight loss during calcination. The conversion of aragonite to calcite occurs between 500°C and 700°C, while optimal decomposition into CaO is achieved at 1000°C. X-ray fluorescence (XRF) analysis indicated reduced impurities in the samples post-calcination. Scanning electron microscopy (SEM) detailed the morphological characteristics of the shell powders, highlighting temperature-dependent surface features. In conclusion, the optimal calcination temperature for extracting calcium from SST shells is 1000°C. The resulting calcium oxide can be a valuable precursor for various material applications. This research contributes to the efficient utilization of biowaste resources, emphasizing the potential of freshwater snail shells in the sustainable production of calcium-derived materials.